2021
DOI: 10.3390/genes12101527
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Peptides Resistance in Staphylococcus aureus: Various Mechanisms and the Association with Pathogenicity

Abstract: Staphylococcus aureus is a bacterium that mainly colonizes the nasal cavity and skin. To colonize the host, it is necessary for S. aureus to resist many antibacterial factors derived from human and commensal bacteria. Among them are the bacteria-derived antimicrobial peptides (AMPs) called bacteriocins. It was reported that some two-component systems (TCSs), which are signal transduction systems specific to bacteria, are involved in the resistance to several bacteriocins in S. aureus. However, the TCS-mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 72 publications
(109 reference statements)
1
7
0
Order By: Relevance
“…S. aureus , a gram-positive bacterium, can cause variety of infections ranging from minor skin and soft tissue infections such as impetigo, folliculitis, and cutaneous abscesses to life-threatening diseases such as sepsis, infective endocarditis or toxic shock syndrome respiratory, tract and bloodstream infections 2 , 3 . Besides, S. aureus can produce a variety of toxins including enterotoxins related to food poisoning, toxic shock syndrome toxin, hemolysin, leukocidin and exfoliative toxins, which generate various diseases ranging from skin infections to systemic life-threatening diseases 4 , 5 . During the past decade, there has been an increasing awareness that S. aureus biofilms are a major cause for concern in multiple infections 6 .…”
Section: Introductionmentioning
confidence: 99%
“…S. aureus , a gram-positive bacterium, can cause variety of infections ranging from minor skin and soft tissue infections such as impetigo, folliculitis, and cutaneous abscesses to life-threatening diseases such as sepsis, infective endocarditis or toxic shock syndrome respiratory, tract and bloodstream infections 2 , 3 . Besides, S. aureus can produce a variety of toxins including enterotoxins related to food poisoning, toxic shock syndrome toxin, hemolysin, leukocidin and exfoliative toxins, which generate various diseases ranging from skin infections to systemic life-threatening diseases 4 , 5 . During the past decade, there has been an increasing awareness that S. aureus biofilms are a major cause for concern in multiple infections 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Agr also represses the expression of apsRS which confers resistance to antimicrobial peptides such as human β-defensin-3, LL37, and bacteriocins (nisin A, nukacin ISK-1) [380]. ApsR regulates the dlt operon that adds alanine to teichoic acid in the cell wall and mprF (fmtC), which adds lysine to phosphatidylglycerol in cell membranes [381][382][383].…”
Section: Tcss In Staphylococcus Aureusmentioning
confidence: 99%
“…This leads to a reduced negative charge of the bacterial surface, and a consequently reduced binding of the positively charged antimicrobial peptides [381][382][383]. Since Agr expression is low during the early phase of bacterial growth, while high in the stationary phase, the susceptibility to antimicrobial peptides changes during cell growth with low susceptibility during the exponential phase and high susceptibility in the stationary phase [380,384].…”
Section: Tcss In Staphylococcus Aureusmentioning
confidence: 99%
“…It was questionable whether highly resistance could evolve if exposed to a high concentration of nisin A. After several experimental trials, finally, some research groups were able to obtain highly nisin A-resistant S. aureus strains with mutations in BraRS, or PmtR when exposing S. aureus to sub-MICs of nisin A ( Blake et al, 2011 ; Arii et al, 2019 ; Kawada-Matsuo et al, 2020 , 2021 ). Arii et al (2019) isolated several nisin A highly resistant S. aureus strains by exposing sub-MIC of nisin A three times and obtained two types of the mutants, with mutations in braRS or pmtR ( Figure 6 ).…”
Section: Emergence Of Resistance To Ampsmentioning
confidence: 99%
“…The braS mutation was found in the histidine kinase region, suggesting that the mutated BraS is autophosphorylated without the stimulation of nisin A. Blake et al also reported the point mutation of NsaS (BraS) in nisin-resistant S. aureus strains. Another nisin A highly resistant S. aureus mutant was isolated by the mutation of PmtR with the increased expression of PmtA-D, an ABC transporter, involved in the susceptibility to nisin A and beta-defensin ( Kawada-Matsuo et al, 2020 , 2021 ). Since PmtR was a negative regulator for PmtA-D expression, the mutated PmtR could not bind to the upstream region of pmtA-D .…”
Section: Emergence Of Resistance To Ampsmentioning
confidence: 99%